Integrated half-bridge switch using 70-μm-thin devices and hollow interconnects - Solomon, Adane Kassa; Li, Jianfeng; Castellazzi, Alberto; Johnson, Christopher Mark (IEEE, 2015)
An application-oriented integration concept for a half-bridge switch assembly has been developed based on the latest generation 70- μm-thin insulated gate bipolar transistors and diodes, which are rated at 600 V/200 A. This paper addresses the design and reliability of the assembly, with a fully bondwireless approach using cylindrical copper bumps. Advanced numerical structural simulation techniques are also applied to assess the influence of interconnect characteristics (material, size, and shape) and try to determine an optimum solution for reducing the stress and creep strain development in the solder joint. Preliminary experimental tests of the power module are also carried out at different switching frequency and loads to prove the validity of the proposed solution in terms of electromagnetic performance.